QUALITY BY DESIGN APPROACH: REGULATORY NEED, CURRENT, AND FUTURE PERSPECTIVE - RAJORA, AAYUSHI; CHHABRA, GURMEET (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Quality by design (QbD) is utilized in the event of pharmaceutical processes to create certain predefined product quality. QbD ideas unit of measurement explained in International Conference on Harmonization (ICH) pointers Q8 (R1) (Pharmaceutical development), Q9 (Quality risk management [QRM]), and Q10 (Pharmaceutical quality system). ICH Q8 (R1) guideline defines QbD as “a systematic approach to develop that begins with predefined objectives and emphasizes product and methodology, understanding, and methodology management, supported sound science and QRM.” QbD approach studied the implications of various input variables (e.g. methodology parameters, and materials) of the merchandise development methodology, on the final word product (active pharmaceutical ingredient or drug product). The late QbD approach integrates the principles of QRM, and methodology analytical technology (PAT). QbD combined with methodology analytical technology (PAT) tools modify methodology management and increase assurance that the merchandise quality attributes unit of measurement achieved consistently. An integrated and risk-based approach for review of the merchandise development methodology is also a future need of the QbD plan. Although implementing the QbD approach is not a restrictive demand, restrictive agencies to supply flexibility in their pointers for producing that unit of measurement developed by the QbD approach. Rising trends embody the growing interest in quantifying and managing the impact of raw materials’ attributes variability of methodology and product, what is more, as a result of the event of retrospective QbD approaches in complement to simple QbD. Thus, the QbD approach is also a tool for developing worth effective and quality pharmaceutical products.